Development and validation of a scale for measuring pet owners loyalty to their pet - Alan, Seda Cavus; Ozen, Abdullah; Halisdemir, Nurhan (Tubitak Scientific & Technological Research Council Turkey, 2023)
Loyalty is a person's willingness to devote oneself to a cause and consists of concepts such as fidelity, not giving up, continuity, and stability. For this reason, this relationship stems from loyalty to be able to talk about a strong attachment between humans and animals. This study aimed to develop a measurement tool for the evaluation of the loyalty levels of people toward their pets. The qualitative method for determining the judgments in the scale will be called the pet loyalty scale; the quantitative methods (explanatory factor analysis and confirmatory factor analysis) were used to determine the validity and reliability of the scale. The qualitative method was carried out with 40 animal owners in Bursa, while both quantitative methods were applied to 580 animal owners in Istanbul, Ankara, and Izmir. The analysis of the results revealed that the total variance explanation rate of the scale was 62.1%, and Cronbach's alpha value was 0.764. Consequently, a 19-item pet loyalty scale consisting of four factors, namely hearty commitment, stability, possibility of giving up, and responsibility, was developed. This scale was considered to have sufficient validity and reliability to measure the loyalty of animal owners to their animals.
Keywords: Animal companion; animal owner; loyalty; pet; scale development